Hypertension in Indonesia in 2018: An Ecological Analysis - Azizah Andzar Ridwanah; Hario Megatsari; Agung Dwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hypertension is a degenerative disease that is often found in conjunction with other degenerative diseases.The study was aimed at analyzing ecologically the factors related to the prevalence of hypertension inIndonesia. The study was conducted using secondary data from the 2018 Indonesia Basic Health Survey.All provinces were taken as samples. Apart from the prevalence of hypertension, 4 other variables analyzedas independent variables were the prevalence of obesity, the percentage of the population with less physicalactivity, the percentage of daily smokers, and the percentage of the population with salty food consumptionhabits ? 1 per day. Data were analyzed using a scatter plot. The results of the study found that the higherthe prevalence of obesity in a province, the higher the prevalence of hypertension in that province. Thehigher the percentage of the population with less physical activity in a province, the higher the prevalenceof hypertension in that province. The higher the percentage of daily smokers in a province, the higher theprevalence of hypertension in that province. The higher the percentage of the population with salty foodconsumption habits ? 1 per day, the higher the prevalence of hypertension in that province. It was concludedthat the four independent variables analyzed ecologically were positively related to the prevalence ofhypertension in Indonesia.